2017
DOI: 10.1007/s00418-017-1623-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the midgut cells in the European cave spider, Meta menardi, during starvation in spring and autumn

Abstract: During the growth period, in surface habitats, spiders catch enough prey to feed normally. In contrast, in the cave entrance zone, prey may be relatively scarce. Meta menardi inhabits this cave section, resulting in temporary starvation. We studied structural changes in the midgut epithelial cells of M. menardi during a short-term and a medium-term controlled starvation to mimic the occasional starvation in caves, during spring and autumn. Digestive cells, secretory cells and adipocytes were examined before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…In this study, we focused on the ultrastructural changes in the midgut diverticle epithelial cells of M. menardi during a four-month winter starvation experiment. These findings enable the completion of the comparative study of responses to starvation in M. menardi in critical phases of the life cycle: the beginning and the end of the growth period 35 with abundant food and winter with scarce food (this study). Our experimental conditions mimic the natural starvation period of M. menardi which occurs if they fail to catch prey during wintertime.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we focused on the ultrastructural changes in the midgut diverticle epithelial cells of M. menardi during a four-month winter starvation experiment. These findings enable the completion of the comparative study of responses to starvation in M. menardi in critical phases of the life cycle: the beginning and the end of the growth period 35 with abundant food and winter with scarce food (this study). Our experimental conditions mimic the natural starvation period of M. menardi which occurs if they fail to catch prey during wintertime.…”
Section: Discussionmentioning
confidence: 98%
“…We asked which are characteristic changes in the midgut diverticle epithelial cells, and which energy-supplying compounds M. menardi spend during overwintering. Finally, we compared findings in M. menardi starved during the growing period with relatively abundant prey 35 , and those starved during the wintertime with much more limited prey availability. This analysis of the whole-year response to starvation in M. menardi could eventually decover some specific features in supporting cells with energy and nutrients in the hypothetically stepwise adaptation to subterranen habitats.…”
Section: Introductionmentioning
confidence: 99%
“…This process should be correlated to the diffusion of ions in the cytosol to the cell membrane, thus it has to be related to the viscosity of cytosol. It is clear that when the organism is in the starvation period, the composition of cytosol is changing [18][19][20]. In the work [9] authors have shown that in the cells group respectively.…”
Section: Relaxationsmentioning
confidence: 99%
“…This suggest the possible origin of this process. Every organism has reserve material mainly in the form of lipid droplets [19,20,24]. Such lipid droplets have been found in the hepatopancreas of Neocaridina davidi shrimps [25].…”
Section: Relaxationsmentioning
confidence: 99%
“…The unique adaptations to the dark and nutrient poor subterranean habitat have fascinated biologists since the dawn of speleobiology more than 200 years ago. Studies have discovered numerous examples of convergent evolution including physiological adaptations such as low metabolic rates and other mechanisms to survive long-term starvation (Hervant et al 1997;Lipovsek et al 2018), and morphological adaptations such as elongation of limbs, loss of eyes and pigments (Poulson and White 1969;Christiansen 2004;Culver and Pipan 2009;Mammola 2018). However, very few studies have looked into behavioural adaptations to the hypogean environment (but see: Juberthie-Jupeau 1988;Hoch and Howarth 1993;Parzefall 2005), likely because in-situ studies of animal behaviour are fraught with difficulties given the scarcity and inaccessibility of most cave organisms.…”
Section: Introductionmentioning
confidence: 99%